Histone H3 Arg2 methylation provides alternative directions for COMPASS. - Klose, R; Zhang, Y (2007)
Post-translational modification of histones can profoundly affect chromatin structure and function. The discovery that histone H3 Arg2 methylation is a widespread silencing modification that inhibits histone H3 Lys4 trimethylation extends our understanding of how active and silenced chromatin states are maintained. © 2007 Nature Publishing Group.